A survey of the ducks breeding at Loch Leven in 1966 - Boyd, H; Campbell, C R G (Wildfowl, 1967)
Seven species of ducks nested on Loch Leven in 1966. Seven hundred and five nests were found, nearly all on one island, of 105 acres: Tufted Duck 323, Mallard 285, Gadwall 41, Wigeon 41, Teal 9, Shoveler 6, and 5 broods of Shelducks. About two-thirds of the nests of dabbling ducks and a third of the Tufted Ducks' nests were known to have been successful. Predation by Jackdaws caused most egg losses, which were heaviest in June. Rough estimates from changes in brood-size suggest that not more than 1,900 young ducks reached the flying stage, about three-fifths of those hatched.